2011
DOI: 10.1002/jso.21927
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection combined with chemotherapy can help achieve better outcomes in patients with primary colonic lymphoma

Abstract: PCL is a rare malignancy of the gastrointestinal tract, and surgical resection should be considered a part of the standard treatment to achieve a better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
2
27
0
5
Order By: Relevance
“…Nonetheless, because that the details of chemotherapy are unavailable from the SEER database, we are incapable to evaluate the actual role of chemotherapy in the treatment of PCL. The present results demonstrated that patients who received surgical intervention exhibited significant survival improvement (113 months versus 74 months, adjusted HR = 0.69, 95% CI: 0.59-0.81) and were consistent with previous study [26], supporting the potential important role of surgery in the comprehensive therapy of PCL.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Nonetheless, because that the details of chemotherapy are unavailable from the SEER database, we are incapable to evaluate the actual role of chemotherapy in the treatment of PCL. The present results demonstrated that patients who received surgical intervention exhibited significant survival improvement (113 months versus 74 months, adjusted HR = 0.69, 95% CI: 0.59-0.81) and were consistent with previous study [26], supporting the potential important role of surgery in the comprehensive therapy of PCL.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that patients were diagnosed at the mean age of 63.9 years with a male predominance (male: female = 1.58: 1), which is similar to previous studies in the West and East [10, 12, 18, 26]. Approximately 41.8% and 21.3% of PCL patients were in Ann Arbor stages IE and IVE, respectively, which is similar to the results from a German multicenter trial [27].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Distant metastasis is the major cause of colon-cancer-related mortality. Although the survival rate of colon cancer patients has improved, the survival of the average patient was less than 20 months [1,2].…”
Section: Introductionmentioning
confidence: 99%